Right-sided obstructed hemivagina ipsilateral renal agenesis (OHVIRA): A case report - Vaishnavi Malarazhagan; Mayooran Veerasingham; Kanapathippillai Sivanesan (Elsevier, 2020)
Introduction: Obstructed hemivagina ipsilateral renal agenesis (OHVIRA) is a rare anomaly of the urogenital system. The characteristic triad of this syndrome, which was initially reported in 1950, is didelphys uterus, obstructed hemivagina, and ipsilateral renal agenesis (Embrey, 1950 [1]). Case: A 17-year-old girl was referred with a 6-month history of offensive vaginal discharge. Magnetic resonance imaging (MRI) established the diagnosis of OHVIRA. She underwent surgery for drainage of the hematocolpos and excision of the vaginal septum followed by an uncomplicated recovery and the patient had normal menstrual cycles after surgery. Conclusion: There should be a high suspicion of OHVIRA syndrome when encountering adolescent patients with non-specific abdominal or pelvic symptoms. Keywords: Mullerian anomaly, Urogenital malformation, OHVIRA, Didelphys and bicollis, Obstructed hemivagina, Renal agenesis